KONSEPSI MORALITAS DAN PENDIDIKAN NILAI DALAM PENDIDIKAN ILMU PENGETAHUAN SOSIAL (IPS) - Poniam Poniam (CV. ADIBA AISHA AMIRA, 2025)
Social Studies education plays a crucial role in shaping students' character and morality, in addition to providing knowledge about society, history, geography, and economics. In the era of globalization, which is full of challenges, Social Studies education must be able to respond to social dynamics such as social inequality and cultural identity changes. One important focus in Social Studies education is strengthening values and moral education, which is often overlooked in the academic context. Value-based and moral education can help create a generation of young people who are not only academically intelligent but also socially conscious and morally responsible. This study aims to explore the integration of value and moral education in Social Studies learning and the challenges and opportunities that arise in its implementation. The research uses a qualitative approach with a literature study method that examines key theories regarding moral education, character development, and the integration of values into the Social Studies curriculum. The findings indicate that value-based education in Social Studies can shape students into individuals who not only understand social concepts but also have the ability to act with integrity, responsibility, and empathy. Overall, value-based education in Social Studies learning has great potential to shape students' character, making them not only knowledgeable but also active contributors to creating a more inclusive, just, and harmonious society